THE EFFECT OF ORGANIZATIONAL COMMITMENTS, UNDERSTANDING OF RISK BASED INTERNAL AUDIT, SUSTAINABLE EDUCATION AND AUDITOR MOTIVATION ON THE PERFORMANCE OF AUDITORS WITH SELF EFFICACY AS MODERATING VARIABLES IN THE SUMATERA UTARA PROVINCE - Rizki, Mela Novita (Asosiasi Dosen Akuntansi Indonesia, 2019)
The objective of this study is to examine the factors that influence the performance of auditors at the Inspectorate of North Sumatra Province with self-efficacy as a moderating variable. This type of research is explanatory research using primary data. The population in the study were 34 functional auditors at the Inspectorate of North Sumatra Province. The data collection method was a census method by distributing questionnaires to obtain a total sample of 34 employees. Testing the research hypothesis using multiple linear regression analysis and testing the moderating variable using a test of the change in the coefficient of determination. The results showed that simultaneous organizational commitment, understanding of risk based internal audit, continuing education and auditor motivation together had a positive and significant effect on auditor performance. Partially the variable organizational commitment, continuing education and auditor motivation have a significant effect on auditor performance while the risk-based internal audit understanding variable has no significant effect on auditor performance. The self-efficacy variable is proven to moderate the relationship between organizational commitment, understanding of risk based internal audit, continuing education and auditor motivation on auditor performance.